Prevalence of Vestibular Dysfunction in Children With Neurological Disabilities: A Systematic Review - Ghai, Shashank; Hakim, Mireille; Dannenbaum, Elizabeth; Lamontagne, Anouk (Frontiers in Neurology, 2019)
Background: In children with neurological or neurodevelopmental conditions, vestibular disorders may co-exist with the primary condition and further contribute to disability and restriction in functional independence and participation. Awareness of their existence may favor an early diagnosis and better treatment outcomes. Objectives: To determine the prevalence of vestibular dysfunction in children and adolescents (3-21 years old) diagnosed with either cerebral palsy (CP), traumatic brain injury (TBI), sensorineural hearing loss (SNHL) or cochlear implantations (CI). Methods: Four researchers systematically reviewed the literature from three databases (EMBASE, MEDLINE, CINAHL) until June 2018. Results: Twenty-four studies were analyzed in this systematic review. A single, high-quality study reports a prevalence of 48.4% of spastic CP children having a saccular dysfunction. Three fair-quality studies report a prevalence of 14.6%-81%, 21 days post-TBI. Twelve poor-to-high quality studies demonstrate a prevalence of 18.7%-96.1% in children with SNHL. A prevalence range of 3%-84% of children with CI is reported by 9 fair-to-high quality studies. Conclusion: Clinicians should be aware of the prevalence of vestibular dysfunction in these populations and implement appropriate assessments to improve treatment outcomes.